Bibliometric analysis of thesis from eight universities of Pichincha, Napo and Orellana (Ecuador) - Estrella, Nancy (2019)
Bibliometric analysis is useful for quantitative and qualitative analysis of scientific-technical publications, as well as establishing topics and research areas. Universities produce scientific and technical knowledge through degree projects developed by their students, but it has not received the same treatment as other dissemination forms such as scientific papers or conference presentations. In this sense, a bibliometric analysis of degree projects on tourism from Universities of Ecuador has not been done. Hence, this research states as objective the systematization of undergraduate and graduate degree projects from eight Universities of Pichincha, Napo, and Orellana provinces, which have programs on tourism, hospitality, and gastronomy. The available information in digital repositories was systematized from the period of 2000 to 2017. Descriptive statistics and bibliometric indexes were applied. As a result, 3.185-degree projects were collected, most of them (98%) were from undergraduate programs. 62% of degree projects were identified and focused on economic and administrative topics based on the private sector mainly in Pichincha (especially in Quito’s Downtown and La Mariscal neighborhoods), Cotopaxi and Imbabura provinces. Community-based and cultural tourism topics, mainly in Highlands and Amazonia, and tourism development for the territories were also addressed. Universities with greater productivity, levels of collaboration and bigger research teams were identified. The literature cited is not up-to-date and it comes mainly from Mexico and Spain. The results obtained can be an important input for public, private, and community sectors and mainly for Academia, which could focus its further researches on topics and least studied areas.